Acceptor–Donor–Acceptor‐Type Orange–Red Thermally Activated Delayed Fluorescence Materials Realizing External Quantum Efficiency Over 30% with Low Efficiency Roll‐Off. Issue 18 (1st April 2021) - Karthik, Durai; Jung, Young Hun; Lee, Hyuna; Hwang, Soonjae; Seo, Bo‐Min; Kim, Jun‐Yun; Han, Chang Wook; Kwon, Jang Hyuk
Abstract: Two new orange–red thermally activated delayed fluorescence (TADF) materials, PzTDBA and PzDBA, are reported. These materials are designed based on the acceptor–donor–acceptor (A–D–A) configuration, containing rigid boron acceptors and dihydrophenazine donor moieties. These materials exhibit a small Δ E ST of 0.05–0.06 eV, photoluminescence quantum yield (PLQY) as high as near unity, and short delayed exciton lifetime (τd ) of less than 2.63 µs in 5 wt% doped film. Further, these materials show a high reverse intersystem crossing rate ( k risc ) on the order of 10 6 s −1 . The TADF devices fabricated with 5 wt% PzTDBA and PzDBA as emitting dopants show maximum EQE of 30.3% and 21.8% with extremely low roll‐off of 3.6% and 3.2% at 1000 cd m −2 and electroluminescence (EL) maxima at 576 nm and 595 nm, respectively. The low roll‐off character of these materials is analyzed by using a roll‐off model and the exciton annihilation quenching rates are found to be suppressed by the fast k risc and short delayed exciton lifetime. These devices show operating device lifetimes (LT50 ) of 159 and 193 h at 1000 cd m −2 for PzTDBA and PzDBA, respectively. The high efficiency and low roll‐off of these materials are attributed to the good electronic properties originatng from the A–D–A molecular configuration. Abstract : Two new orange–red thermally activated delayed fluorescence (TADF) materials, PzTDBA and PzDBA, are developed based on the acceptor–donor–acceptor configuration. The TADF devices fabricated with 5 wt% PzTDBA and PzDBA as emitting dopants show maximum external quantum efficiency (EQE) of 30.3% and 21.8% with extremely low roll‐off of 3.6% and 3.2% at 1000 cd m −2 . The high efficiency and low roll‐off is due to the high photoluminescence quantum yield (PLQY) and short delayed exciton lifetime.